Alginates and Their Biomedical Applications (Springer Series in Biomaterials Science and Engineering,, 2018)
This book presents a comprehensive review of the latest advances in developing alginate-based biomaterials and derivatives as well as their biomedical and pharmaceutical applications. It covers the physiochemical properties of alginates, production and formulation methods, derivatizations and characterization methods, the fundamental work on optimizing alginate polymers for defined biomedical purposes as well as the scope and effectiveness of their applications in medicine and therapeutic approaches. The book brings together new concepts and advances in harnessing alginate-based biomaterials in combination with applied technological advances to tailor their applications to medical needs. The contributions by leading academics, clinicians and researchers not only cover the fundamentals, but also open new avenues for meeting future challenges in research and clinical applications.